อิทธิพลของการรับรู้ความสามารถของตนเองที่มีต่อผลสัมฤทธิ์ทางทหารของนักเรียนนายร้อยโดยมีความเพียรและสุขภาวะเป็นตัวแปรส่งผ่าน - ปวริศ ไชยลาโภ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The purposes of this research were 1) to study the level of self-efficacy, grit, well-being, and cadet military achievement, 2) to examine the goodness of fit of the structural equation modeling of effects of self-efficacy on military achievement of cadet students which grit and well-being as mediators with the empirical data, and 3) to analyze the role of mediators of grit and well-being of the structural equation modeling of effects of self-efficacy on military achievement of cadet students. The participants were 805 second to fifth-year cadet students and chosen by stratified random sampling. Research instruments were a self-efficacy scale, a grit scale, and a well-being scale. Data were analyzed using LISREL Program for Structural Equation Modeling (SEM).          Findings were as follows:          1) Overall, the cadet students had a high level of well-being (%RWB = 70.00) whereas their cadet military achievement, grit, and self-efficacy are at a moderate level (%RCMA = 47.25; %RGRT = 44.00; %RSE = 35.00).          2) The result from the Structural Equation Modeling indicated that the model fit well to the empirical data (Chi-Square = 44.620, df = 36, p = 0.131, Chi-Square/df = 1.239, GFI = 0.991, AGFI = 0.978, NFI = 0.997; RMR = 0.015, RMSEA = 0.018).          3) Self-efficacy had direct influence on cadet military achievement (β = 0.765, p < .05) whereas grit had a negative effect on cadet military achievement (β = -0.704, p < .05). However, there was no significant effect of well-being on cadet military achievement.